Boron in Prebiological Evolution. (22nd January 2021) - Franco, Ana; da Silva, José Armando L.
Abstract: Boron(III), as borate (or boric acid), mediates the synthesis of ribose, ribonucleosides, and ribonucleotides. These reactions are carried out under moderate temperatures (typically 70–95 °C) with organic molecules (or their derivatives) detected in interstellar space and inorganic ions found in minerals on Earth (and could occur during early stages of prebiotic evolution). Research in this century suggests that borate was a relevant prebiological reagent, thus reinforcing the RNA world hypothesis as an explanation for the origin of life. Herein, these developments on prebiological chemistry related to boron species are reviewed. Abstract : Research suggests that borate could have mediated the prebiotic synthesis of RNA precursors (ribose, ribonucleosides, and ribonucleotides) in reactions relevant for the origin of life. This minireview provides an overview of recent developments in prebiological chemistry related to boron species.